Felicity Condition of the Speech Act in Raya and the Last Dragon Movie: Pragmatics - Alifya Muhamad; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This study aims to identify the types of felicity condition in the Raya and The Last Dragon movie. This study used a qualitative method in which the data collected by watching the movie and transcribe the dialogue performed by the characters. The data that is used in this paper are Raya and The Last Dragon movie and its transcript. The findings revealed five types of felicity condition which is essential condition (21.27 %), sincerity condition (27.65 %), preparatory condition (17.02 %), propositional content condition (23.4 %), and general condition (10.63 %).